Performance Efficiency of Muhammadiyah University Sumatera Area Using Data Envelopment Analysis (DEA) - Sulistyandari, Sulistyandari; Fikri, Khusnul; Puji, Ari Andriyas; Abdullah, Dahlan (ADPEBI Publisher, 2023)
Purpose – This paper seeks to examine the efficacy of predicting turnover for employees and entrepreneurs from Estonia, Latvia, and Lithuania using attitudes towards benefits, pay satisfaction, pay, gender, and age across a four-year time frame. Methodology/approach – A survey that included information on attitudes towards benefits and pay satisfaction was used to collect data from 153 Estonian, 157 Latvian, and 146 Lithuanian employees and 243 Latvian, 103 Estonian, and 109 Lithuanian entrepreneurs. Findings – It was found that . Attitudes towards benefits were generally significant predictors of turnover for employees and entrepreneurs over a four-year time period while satisfaction with pay was typically significant for employees but not for entrepreneurs. Novelty/value – As employee retention has been an important factor in the Baltic region over the last two decades it is vital to understand how to retain employees. Keywords Employee turnover, Entrepreneurs, Pay, Estonia, Latvia, Lithuania.